Rising and falling diapirs, shifting depocenters, and flap overturning in the Cretaceous Sopeira and Sant Gervàs subbasins (Ribagorça Basin, southern Pyrenees). Issue 3 (15th March 2016) - Saura, Eduard; Ardèvol i Oró, Lluís; Teixell, Antonio; Vergés, Jaume
Abstract: The halokinetic structure of inverted salt‐related continental margins is frequently obliterated by compressional overprinting. The Cretaceous Sopeira and Sant Gervàs subbasins of the Ribagorça Basin (south central Pyrenees) show evidence of salt‐related extensional tectonics and diapiric growth along the Iberian Margin of the Mesozoic Pyrenean rift. We present an integrated field‐based tectonic‐sedimentary study to reconstruct the evolution of the Ribagorça Basin system previous to, and in the early stages of, the Pyrenean orogeny. The ~4 km thick Albian‐Cenomanian Sopeira minibasin infill thins toward the basin borders, especially toward the eastern, N‐S trending, Llastarri salt weld. The 90° tilt to the south of the Sopeira basin bottom records the growth of the buried north dipping Sopeira listric fault from Albian to Santonian times, when it evolved as an extensional rollover associated with the Aulet salt roller. The ~3 km thick Cenomanian‐Campanian succession filling the Sant Gervàs flap displays 130° bed fanning attitude from overturned Cenomanian carbonate platform strata to upright Campanian turbidite beds. The Sant Gervàs flap development since Cenomanian times was related to the fall of a large salt pillow after the main Soperia minibasin stage. Jurassic‐Campanian diachronous subsidence is also observed in the adjacent Montiberri, Faiada, and Tamurcia depocenters. Correlation with the Pedraforca, Cotiella, and Basque‐Cantabrian Basins along the southern Pyrenees suggests that a significant segment of the Iberian side of the Pyrenean rift experienced a gravity‐driven extension from Albian to late Santonian. The Ribagorça Basin provides an excellent field analogue for presently buried salt‐related structures of extended passive margins. Key Points: Protracted halokinesis from Cretaceous extension to compression is recorded in Ribagorca Basin Diachronous Ribagorca Basin depocenters were part of a large diapiric province in southern Pyrenees Gravitational extension ruled the South Pyrenean rift margin from late Albian to late Santonian